2020
DOI: 10.1371/journal.pone.0242209
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and compost effects on soil microbial communities and nitrogen induced respiration in turfgrass soils

Abstract: We examined the effect of a labile soil amendment, compost, and recalcitrant biochar on soil microbial community structure, diversity, and activity during turfgrass establishment. Two application rates of biochar (B1 at 12.5 t ha-1and B2 at 25 t ha-1), a 5 centimeter (cm) green waste compost treatment (CM) in top soil, a treatment with 12.5 t ha-1 biochar and 5 cm compost (B1+CM), and an unamended control (CK) treatment were prepared and seeded with tall fescue. Overall, results of phospholipid fatty acid anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 72 publications
3
24
1
Order By: Relevance
“…Achmon et al (2020) [204] also reported a highly significant drop in the relative abundance of plant pathogenic fungal taxa. These results, in turn, may imply that compost is able to "re-write" the microbiome of a soil, or replenish a partially missing or dysfunctional microbiome, and thus, the addition of compost can be used to achieve specific goals, as suggested by Azeem et al (2020) [200] in the case of turfgrass soil.…”
Section: The Impact Of Mgwc On Microbial Lifementioning
confidence: 98%
See 1 more Smart Citation
“…Achmon et al (2020) [204] also reported a highly significant drop in the relative abundance of plant pathogenic fungal taxa. These results, in turn, may imply that compost is able to "re-write" the microbiome of a soil, or replenish a partially missing or dysfunctional microbiome, and thus, the addition of compost can be used to achieve specific goals, as suggested by Azeem et al (2020) [200] in the case of turfgrass soil.…”
Section: The Impact Of Mgwc On Microbial Lifementioning
confidence: 98%
“…Although microbial activity plays a crucial role in the formation and maturation of compost [146], and the addition of organic amendments increases microbial biomass [154,160,199] and may induce major changes in the species composition and abundance of microbial communities [200], partly due to its strong correlation with its high organic matter, Ca, Mg and K content [155], the biological interactions between the soil microbiome and the microbial species composition of organic amendments, including MGW, have not yet been satisfactorily explained. The reason for this may be, for example, the different content (quality and quantity) of biologically active substances in MGW, which depends on the plant-species composition of MGW.…”
Section: The Impact Of Mgwc On Microbial Lifementioning
confidence: 99%
“…Their addition to soil can be a big plus to soil health and sustainable crop production. It is worth noting that a combination of the biochar, compost, and fruit juices could be more beneficial to soil health rather than the individual agro-wastes [64], which can only be ascertained through amending soils in the field.…”
Section: Characteristics Of the Kitchen Waste Compost And Potential Benefits To Soil Healthmentioning
confidence: 99%
“…Different soil treatments using organic material containing mixed microbial communities have shown efficacy to suppress different diseases in turfgrass. Among those, compost has been used very successfully [94][95][96][97][98][99][100][101][102]. While adding compost might have positive effects, results can be irreproducible due to its microbial and chemical diversity and complexity.…”
Section: Microbial Products For Turfgrassesmentioning
confidence: 99%